A Retrospective Comparison of Preoperative Estimated Glomerular Filtration Rate as a Predictor of Postoperative Cardiac Surgery Associated Acute Kidney Injury - Karim, Habib Md Reazaul (Ann Card Anaesth, 2020)
BACKGROUND: Cardiac surgery-associated acute kidney injury (CSA-AKI) remains common with distressingly high mortality. Over time, risk scorings systems have been developed to predict it and preoperative low estimated glomerular filtration rate (eGFR) has been regarded as one of the predicting risk factors. OBJECTIVES: The present study is aimed at assessing the relation of different ranges of preoperative eGFR with an incidence of CSA-AKI defined by the AKI network (AKIN) criteria. MATERIALS AND METHODS: Files of 134 patients with eGFR of >40 cc/min/1.73 m(2) body surface area (BSA) who underwent cardiac surgeries on cardiopulmonary bypass were screened for data collection. Occurrences of CSA-AKI were evaluated as per the AKIN criteria over the course of 3 postoperative days. The relationships of different ranges of preoperative eGFR with CSA-AKI were analyzed by appropriate statistical tests using Instat software and P < 0.05 was considered statistically significant. RESULTS: A total of 60 males and 74 females with a mean + standard deviation (SD) age of 37.98 ± 12.50 years and mean + SD preoperative eGFR of 70.20 ± 20.89 cc/min/1.73 m(2) were analyzed in this study. About 49.25% of patients suffered from CSA-AKI by the 3(rd) postoperative day. The crude risk of CSA-AKI in patients with eGFR 40–60 cc/min/1.73 m(2) was not higher (odds ratio 0.29) as compared to patients in patients with eGFR >100 cc/min/1.73 m(2). The CSA-AKI trend with different eGFR was also statistically insignificant (P > 0.05). CONCLUSION: In patients with preoperative eGFR >40 cc/min/1.73 m(2) BSA, a lower preoperative eGFR (40–60 cc/min/1.73 m(2)) does not predict higher incidence of CSA-AKI as defined by AKIN criteria as compared to higher preoperative eGFR (>100 cc/min/1.73 m(2)). Lower height is independently associated with higher incidence of CSA-AKI in such patients.